2012
DOI: 10.1159/000342196
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Topical Coenzyme Q<sub>10</sub> and Vitamin E <smlcap>d</smlcap>-α-Tocopheryl Polyethylene Glycol 1000 Succinate after Cataract Surgery: A Clinical and in vivo Confocal Study

Abstract: Purpose: To evaluate the postoperative effects of topical coenzyme Q10 + vitamin E d-α-tocopheryl polyethylene glycol 1000 succinate (CoQ10) aftercataract surgery. Methods: 40 consecutive patients were randomized to receive CoQ10 or saline solution (SS) twice daily for 9 months after uneventful cataract surgery with a temporal port. Before surgery, on day 14 and at months 3, 6 and 9, they underwent non-invasive break-up time (NIBUT) testing, Schirmer test, BUT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 48 publications
4
19
0
1
Order By: Relevance
“…Darwish et al [6] investigated nerve regeneration after penetrating keratoplasty and suggested that - in the apparent absence of subbasal nerves - the postoperative recovery of central corneal sensitivity could be explained by the presence of epithelial nerves and/or by thinner subbasal nerve fibers that could not be detected by IVCM. In our dataset, corneal sensitivity did not correlate with nerve fiber number, thus confirming our previous findings [8]. This may be explained according to three hypotheses: (1) the presence of regenerated epithelial nerves and/or thin subbasal nerve fibers that could not be detected by IVCM (as in the case of corneal transplants); (2) the lack of correlation between corneal sensitivity and density of subbasal plexus nerve fibers, as reported by Patel et al [29] in normal corneas; and (3) the vicarious role of nerve fibers of the other, unaffected corneal quadrants.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Darwish et al [6] investigated nerve regeneration after penetrating keratoplasty and suggested that - in the apparent absence of subbasal nerves - the postoperative recovery of central corneal sensitivity could be explained by the presence of epithelial nerves and/or by thinner subbasal nerve fibers that could not be detected by IVCM. In our dataset, corneal sensitivity did not correlate with nerve fiber number, thus confirming our previous findings [8]. This may be explained according to three hypotheses: (1) the presence of regenerated epithelial nerves and/or thin subbasal nerve fibers that could not be detected by IVCM (as in the case of corneal transplants); (2) the lack of correlation between corneal sensitivity and density of subbasal plexus nerve fibers, as reported by Patel et al [29] in normal corneas; and (3) the vicarious role of nerve fibers of the other, unaffected corneal quadrants.…”
Section: Discussionsupporting
confidence: 92%
“…diabetes) for neuropathy. Such findings are similar to those of our previous study, in which a 2.7-mm temporal port was chosen [8]. …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations